Blogging at Blackprof - Paul Butler (Washington University Law Review, 2006)
Commenting on the papers by Doug Berman Lawrence Solumn, this paper raises questions concerning the emergence of blogging and its relationship with legal scholarship. These insights suggest that blogging can reach a wider audience and introduce a new way of connecting to certain issues in a way that law reviews cannot reproduce.
Keywords: Blogs; Law – Study & amp; teaching; Legal literature; Minority college faculty; United States